A study on the secular change of residents' population structure in different housing types in a suburb of Tokyo. Issue 3 (25th March 2018) - Lee, Yonggeun; Otsuki, Toshio
Abstract: This study aims to clarify the secular change of population structure by housing type and the resident movement, which is thought to be the primary cause of the population structure's secular change. The study focuses on population indices such as aging rate, average age, age structure, and the rate of continuous living households (C.L.H) at the newly built house stage. Through this study, the following points have been clarified: first, there is no big difference in the population structure indices of residents living in newly built houses irrespective of housing types. However, a difference in population structure occurs and gets larger as time progresses. Second, in the case of detached houses at the 35‐year‐old stage, the rate of C.L.H is 56.8%. On the other hand, the rate of C.L.H at the 35‐year‐old stage is 17.5% in condominiums and 0.8% in rental apartments. Third, it is thought that, because of the difference in the rate of C.L.H, population structure of residents living in 35‐year‐old houses varies due to secular change depending on housing types. Abstract : The secular change of residents' age structure by housing type.